Pelatihan Perancangan Sistem Pencatatan Keuangan KAS Sederhana untuk UMKM Jastip - Gilbert Alexander Hendrik Sipahelut; Jayus Amirullah Parera; Sri Rahayuningsih (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This training is designed to equip jastip MSMEs with knowledge and skills in designing a simple cash financial recording system. By participating in this training, participants are expected to be able to increase the efficiency of business financial management, make better decisions based on accurate data, and ultimately, develop the jastip business